MicroRNA-15a-5p mediates abdominal aortic aneurysm progression and serves as a potential diagnostic and prognostic circulating biomarker - Greg Winski; Ekaterina Chernogubova; Albert Busch; Suzanne M. Eken; Hong Jin; Moritz Lindquist Liljeqvist; Tooba Khan; Alexandra Bäcklund; Valentina Paloschi; Joy Roy; Rebecka Hultgren; Christine Brostjan; et al. (Communications Medicine)
Abstract Background MicroRNAs are post transcriptional modulators of gene expression. We explored the diagnostic and prognostic value of circulating microRNAs in abdominal aortic aneurysm (AAA) disease, for which currently no established circulating biomarker is available. Methods We profiled the expression of 754 human microRNAs in plasma from 187 patients with AAA and 190 matched non-diseased controls. To validate, we used two additional AAA patient cohorts, looking at circulating and aortic tissue-derived microRNA expression, and their correlation to AAA disease phenotype, as well as two murine AAA models. Results We show that among 12 differentially expressed microRNAs, miR-15a and −659 are the most significantly up-regulated in AAA, whereas miR-1183 and -192 are the most significantly down-regulated. miR-15a is upregulated AAA patient tissues, and in plasma from two murine AAA models. In patients from three different cohorts, miR-15a expression levels in plasma, serum and aortic tunica media are significantly correlated with AAA diameter. Through modulation of miR-15a in human aortic smooth muscle cells, we identify several potential target genes of miR-15a known to be down-regulated in human AAA, suggesting its potential involvement in AAA pathology. Inhibition of miR-15a in vivo demonstrates a significant inhibition of murine aortic diameter growth at day 7. Conclusions Our findings suggest that miR-15a is a potential biomarker of AAA. Through in vivo studies and based on its target profile, we show that miR-15a is involved in AAA pathogenesis and could help treatment, but also assist in risk-stratification of AAA patients and identify candidates for early AAA repair.